Causal Factors Influencing Purchase Intention Pet Products on Shopee Application of Consumer in Thailand - Choosawat, Phattiya; Pankham, Sumaman (Journal of Multidisciplinary in Humanities and Social Sciences, 2023)
At the present time, people are likely to love pets, and demand for pet products has continued to increase. The article aimed to 1) develop and validate a causal relationship model of pet products on the Shopee Application of consumers in Thailand; and 2) study the causal factors influencing the customer purchase intention of pet products on the Shopee application in Thailand. This study was quantitative research. This study was quantitative research. The sample consisted of 400 people who have bought pet products on the Shopee application and live in Thailand. The tools used in the research were online questionnaires. The statistics used in data analysis were frequency, percentage confirmatory factor analysis, and the structural equation model. The results of this research were that the development of the causal relationship models consisted of 4 components: 1) perceived quality; 2) awareness; 3) trust; and 4) purchase intention, and the model was consistent with the empirical data to a great extent. The statistic shows CMIN/df = 1.97, GFI = 0.93, AGFI = 0.90, SRMR = 0.05, RMSEA = 0.05, and the forecasting coefficient = 0.44, indicating that the variables in the model can explain the variance of the purchase intention of pet products on the Shopee application by 44 percent. It was found that awareness had a direct influence on purchase intentions. Entrepreneurs who sell pet products on the Shopee application raise awareness among consumers to generate their purchase intentions in the future.